The Concept of Value in De Saussair Linguistics and their Extension in the Book (Arabic Language, Its Meaning and Structure) by Tammam Hassan (Journal of the College of Education for Women, 2019)
This research was distributed into two sections, the first section was concerned with the concept of value for De Saussair and its methodological impact on his linguistic structural conceptions with respect of the distinction between synchronism and diachronism, the value role of linking function between the sounds and the though, the basing of his theoretical conception on the language being a form and not a material according to this principle and the value impact on the demonstration that the linguistic element acquires its functional importance from the relations inside the language system. It also stopped at the methodological impact of value on defining the analytical linguistic unit and the value role in semantics through the principle opposition and the relations among the systems vocabulary; addressing the issue of linguistic synonymy as the most important truth that can be treated within the view of the concept of value. As for the second section, it was concerned with the concept of value for Tammam Hassan in his book (Arabic Language, Its Meaning and Structure) explaining the crystallization of the Arabic term of value and the conformity extent of its concept to the theoretical origin of De Saussair showing the precedence of Hassan in terminology and the theoretical receipt of this concept, then the second section addressed the notes recorded by Hassan against the Arab linguists in their heritage explaining conceptions by his basing on the concept of value. The research followed the descriptive analytical methodology for Hassan which was based on the principle of value in distinguishing among the system levels (phonetics, morphology, syntax) revealing the greatvariance between the Saussairian theoretical origin and the applied dimension for Hassan, then it stopped at the issue of lexicon for Hassan and not considering it a system of the language subsystems. The research criticized this conception within the light of the value concept .